An Analysis of Rhetorical Devices in Taylor Swift’s All Too Well (10-minute version) - Nor Diana Adlin Zainuddin; Nadia Anuar (Development in Language Studies, 2022)
This study aims to identify the rhetorical devices used in Taylor Swift’s single All Too Well (10 Minute Version). The theoretical framework by Knickerbocker and Reninger (1963) was adopted as the theoretical foundation of the study. A qualitative approach was employed in this research through the use of content analysis. Deductive coding was employed in the song analysis and this song was analysed for ten (10) types of rhetorical devices which are (1) simile, (2) personification, (3) hyperbole, (4) metaphor, (5) synecdoche, (6) metonymy, (7) irony, (8) allusion, (9) paradox, and (10) symbol. The analysis revealed that simile and metaphor were the primary rhetorical devices used in this song as four excerpts were identified from the song respectively. Synecdoche, irony, allusion, and paradox were least used in the song as only one excerpt for each rhetorical device. The findings derived from this current study are hoped to narrow the gap in the semantic literature due to the novelty of this song since it was recently released.